E-003 Endovascular Embolisation of Paediatric High-Flow Vertebral Arteriovenous Fistula: Association with Intracranial Steal and the Importance of Post-procedural Management. (14th July 2013) - Honarmand, A; Soltanolkotabi, M; Ansari, S; Rahman, O; Hurley, M; Schoeneman, S; Patel, B; Shaibani, A
Abstract : Purpose and Background: High-flow vertebral artery arteriovenous fistula (VAVF) and concurrent steal from intracranial arteries or contralateral vertebral artery is a well-known phenomenon. Cardiovascular and/or neurological complications following the occlusion of VAVFs have always been a concern in the treatment of VAVFs. Our purpose is to describe a unique asymptomatic presentation of a spontaneous high-flow VAVF in a child associated with flow reversal in the BA requiring endovascular coil embolisation with an emphasis on post-procedural management. Case Report: An 8-year-old boy presented to the emergency department with fever and lethargy. No relevant clinical signs or symptoms were noted except for a prominent palpable pulse on the right side of the neck. There was no history of trauma to the head and neck or connective tissue disorders. Imaging Findings: digital subtraction angiography (DSA) demonstrated a high-flow AVF between the distal portion of the right cervical VA at the level of the proximal transverse foramen of C2, draining into a very large recipient paraspinous venous pouch. Significant enlargement of the right VA was observed at and above the level of the shunt with retrograde supply across the hypertrophied left VA and vertebrobasilar junction into the right VA V4 segment. Selective DSA also demonstrated an enlarged right deep cervical artery supplying the AVF and an enlarged left costocervical trunk augmenting collateral supply to the left VA. There was no antegrade visualisation of the BA from either the vertebral or costocervical/thyrocervical injections, due to the significant steal towards the AVF. Right internal carotid DSA demonstrated reversal of flow in the BA via a large right posterior communicating artery. Treatment and Post-procedural Management: Under general anaesthesia, endovascular coil embolisation using the contralateral vertebral artery approach allowed the controlled complete obliteration of the VAVF, preservation of the reconstituted distal vertebral artery, and restoration of antegrade flow in the vertebrobasilar circulation. The patient was left intubated and sedated for 18 hours in the paediatric intensive care unit for strict haemodynamic control and prophylactic heparin intravenous infusion. Jugular pulsation and blood pressure were strictly monitored with nicardipine infusion to maintain a 25% reduced mean arterial pressure of 50–60 mmHg. Subsequently, the patient was extubated and weaned off the nicardipine remaining normotensive. The patient's hospital course was uncomplicated and he was discharged on post-embolisation day 2. Summary: To the best of our knowledge, association of VAVF with basilar artery (BA) steal in the paediatric population has not been reported. Various types of complications have been reported following abrupt occlusion of high-flow VAVFs including cardiovascular disturbance, neurological dysfunction posing risks for autoregulatory dysfunction and/or reperfusion injury, and neurovascular ischaemic events. Several theories have been proposed to describe the neurological complications occurring following the treatment of high-flow VAVFs including normal pressure perfusion break-through phenomenon, occlusive hyperaemia, and leftward adaptive displacement of the autoregulatory curve. Summing up, methodical angiographic and interventional technique, understanding of complex AVF anatomy, and strict haemodynamic and blood pressure monitoring in neuro-intensive care unit are essential to obtain technical success and minimise complications. Disclosures: A. Honarmand: None. M. Soltanolkotabi: None. S. Ansari: None. O. Rahman: None. M. Hurley: None. S. Schoeneman: None. B. Patel: None. A. Shaibani: None.